Changing geo‐ecological functions of coral reefs in the Anthropocene. (18th December 2018) - Perry, Chris T.; Alvarez‐Filip, Lorenzo
Abstract: The ecology of many coral reefs has changed markedly over recent decades in response to various combinations of local and global stressors. These ecological changes have important implications for the abundance of taxa that regulate the production and erosion of skeletal carbonates, and thus for many of the geo‐ecological functions that coral reefs provide, including reef framework production and sediment generation, the maintenance of reef habitat complexity and reef growth potential. These functional attributes underpin many of the ecosystem goods and services that reefs provide to society. Rapidly changing conditions of reefs in the Anthropocene are likely to significantly impact the capacity of reefs to sustain these geo‐ecological functions. Although the Anthropocene footprint of disturbance will be expressed differently across ecoregions and habitats, the end point for many reefs may be broadly similar: (a) progressively shifting towards net neutral or negative carbonate budget states; (b) becoming structurally flatter; and (c) having lower vertical growth rates. It is also likely that a progressive depth‐homogenisation will occur in terms of these processes. The Anthropocene is likely to be defined by an increasing disconnect between the ecological processes that drive carbonate production on the reef surface, and the net geological outcome of that production, that is, the accumulation of the underlying reef structure. Reef structures are thus likely to become increasingly relict or senescent features, which will reduce reef habitat complexity and sediment generation rates, and limit reef potential to accrete vertically at rates that can track rising sea levels. In the absence of pervasive stressors, recovery of degraded coral communities has been observed, resulting in high net‐positive budgets being regained. However, the frequency and intensity of climate‐driven bleaching events are predicted to increase over the next decades. This would increase the spatial footprint of disturbances and exacerbate the magnitude of the changes described here, limiting the capacity of many reefs to maintain their geo‐ecological functions. The enforcement of effective marine protection or the benefits of geographic isolation or of favourable environmental conditions ("refugia" sites) may offer the hope of more optimistic futures in some locations. A >plain language summary is available for this article. Abstract : Plain Language Summary Foreign Language Abstract: Resumen: La ecología de muchos arrecifes de coral ha cambiado notablemente en las últimas décadas en respuesta a combinaciones de factores de estrés locales y globales. Estos cambios ecológicos tienen implicaciones importantes para la abundancia de taxones que regulan la producción y la erosión de esqueletos de carbonato de calcio, y por lo tanto, para muchas de las funciones geo‐ecológicas clave que brindan los arrecifes de coral, incluida la construcción del marco arrecifal, la generación de sedimentos, el mantenimiento de la complejidad del hábitat y el potencial de crecimiento del arrecife. Estos atributos funcionales también sustentan muchos de los bienes y servicios del ecosistema que los arrecifes proporcionan a la sociedad. Es probable que las condiciones cambiantes de los arrecifes en el Antropoceno afecten significativamente la capacidad de los arrecifes de mantener estas funciones geo‐ecológicas. Si bien la huella de perturbación del Antropoceno se expresará de manera diferente en diferentes ecoregiones y hábitats, el punto final de muchos arrecifes puede ser muy similar: (a) cambiando progresivamente hacia estados con presupuesto de carbonato neutro o negativo netos; (b) reducir su complejidad estructural; o (c) tener menores tasas de crecimiento vertical. También es probable que se produzca una homogeneización de profundidad progresiva en términos de estos procesos y atributos. Es probable que el antropoceno se defina por la desconexión entre los procesos ecológicos que determinan la producción de carbonato en el arrecife y el producto geológico neto de esa producción, es decir, la acumulación de estructuras arrecifales. Es posible, por lo tanto, que las estructuras arrecifales no se renueven (se vuelvan cada vez más decrépitas), lo que perjudicará su capacidad de mantener la complejidad del hábitat, altas tasas de generación de sedimentos y en términos generales limitaría el potencial de crecimiento vertical, limitando así el potencial de alcanzar el aumento del nivel del mar. En ausencia de factores de estrés permanentes, se ha observado la recuperación de comunidades de corales degradadas, lo que resulta en la recuperación de presupuestos netos positivos. Sin embargo, se prevé que la frecuencia e intensidad de los eventos de blanqueamiento relacionados al cambio climático aumentarán en las próximas décadas, lo que aumentaría la magnitud de los cambios descritos aquí. Limitando, así la capacidad de muchos arrecifes de mantener sus funciones geo‐ecológicas. La aplicación efectiva de la protección marina, los beneficios del aislamiento geográfico o de las condiciones ambientales favorables (sitios de "refugio") pueden ofrecer esperanza de un futuro más optimista en algunos lugares.